The Effect of Income, the Role of the Government, and Cleric on the Decision to Pay Professional Zakat in Pekanbaru City - Misdawita, Misdawita; Widayatsari, Any; Asrina, Putri (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The problem of poverty in countries with a Muslim majority can be overcome by optimizing the utilization of zakat. One form of zakat that has great potential to be optimized is income zakat or professional zakat. According to the Pekanbaru Baznas, the potential for zakat could reach Rp90 billion. The method of data analysis in this study is to use a binary logistic regression model. This method was chosen because it is a standard analytical method when the outcome variable is dichotomous and is measured with a value of 1 or 0, where 1 = decision to pay professional zakat and 0 = decision not to pay professional zakat. The results of this study are the income variable has a positive and significant effect on Muzakki's decision to pay professional zakat in Pekanbaru City, which is 35.6%. However, the role of the government and the role of the ulama have no significant effect on Muzakki's decision to pay professional zakat in Pekanbaru City. Based on the research that has been done, it can be concluded that the variables of income, the role of the government, and the role of the ulama together have a significant effect, but partially the role of the government and the role of the ulama have no significant effect on Muzakki's decision to pay professional zakat in Pekanbaru City. Thus, in making a decision to pay professional zakat